الاستعجال بيـن المشـروع والممنـوع في فقه العبادات: Urgency Between the Project and the Forbidden in the Jurisprudence of Worship - Bandar Talal J. Mahallawi (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2021)
ملخص يتناول هذا البحث التطبيقات الفقهية والمسائل التي تندرج في باب الاستعجال بالنظر إلى المشروع منه والممنوع، ومن هنا جاءت هذه الدراسة لبيان المبدأ الذي يوصل إليه نظر الفقه الإسلامي في شأن الاستعجال وحكم أداء المكلف للواجبات الذي لا يخلو من أوجه تدور بين التعجل في الامتثال أو التراخي في الأداء. لذا فقد اعتنى البحث بدراسة المسائل الفقهية المتعلقة بالاستعجال المشروع في فقه العبادات منها مسائل في أبواب الصلاة والصيام والزكاة والحج وكذلك المسائل المتعلقة بالاستعجال الممنوع في هذه الأبواب. واتبع الباحث المنهج التحليلي المقارن من خلال تتبع آراء الفقهاء وأقوالهم واستدلالاتهم ومناقشتها ونقدها وتقويمها، وكان مما توصّل إليه الباحث أن الإسلام نظر إلى الاستعجال نظرة منصفة فذمه في مواضع وحمده في مواضع أخرى بناء على ما تحكمه النصوص الشرعية من الكتاب والسنة والأثر والمعقول والقياس والاستحسان، كذلك فإن تحذير النبي ﷺ من العجلة وأنها من الشيطان يتبين أنه ليس على عمومه. الكلمات المفتاحية: الاستعجال، فقه، فقه العبادات. Abstract This research deals with jurisprudential applications and issues that fall under the section of urgency in view of what is legitimate and what is prohibited. Hence, this study came to clarify the principle that Islamic jurisprudence leads to regarding urgency and the ruling on the performance of duties, which is not without aspects that revolve between haste in compliance or laxity in the performance. Therefore, the research was concerned with studying the jurisprudential issues related to the legitimate urgency in the jurisprudence of worship, including issues in the chapters of prayer, fasting, zakat and pilgrimage, as well as issues related to the urgency prohibited in these chapters. The researcher followed the comparative analytical method by following the opinions, sayings, and inferences of the jurists, discussing, criticizing and evaluating them, and what the researcher reached was that Islam looked at urgency in a fair way, and praised it in places and praised it in other places based on what is governed by the legal texts of the Qur’an and Sunnah, impact, reasonable, analogy and approval, as well. The warning of the Prophet, peace and blessings be upon him, about haste and that it is from Satan, it is clear that it is not general. Keywords: urgency, jurisprudence, jurisprudence of worship.